Coronary collaterals provide more than half of normal perfusion in patients with coronary artery disease - quantification by myocardial perfusion SPECT during elective balloon occlusion. (8th February 2021) - Harris, B; Warren, S; Persson, E; Bhindi, R; Ringborn, M; Ugander, M; Allahwala, U
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: The coronary collateral circulation is a preformed network of anastomotic connections acting as a "natural bypass" mechanism. Whilst the prevalence of collaterals varies between species, approximately 25% of patients have angiographically visible robust collaterals at the time of ST elevation myocardial infarction. While the presence of collaterals is associated with improved outcomes, the magnitude of myocardial perfusion which can be provided by the collateral circulation remains uncertain. PURPOSE: The aim was to quantify collateral myocardial perfusion during experimental coronary balloon occlusion in patients with CAD. METHODS: The study was approved by the local investigational review board, and all patients provided informed consent. Patients without prior infarction, bypass surgery, or angiographically visible collaterals undergoing elective percutaneous transluminal coronary angioplasty (PTCA) to a single epicardial vessel, underwent two scans with 99mTc-sestamibi myocardial perfusion single-photon emission computed tomography (SPECT). All subjects underwent at least three minutes of angiographically verified complete balloon occlusion, at which time an intravenous injection of the radiotracer was administered, followed by SPECT imaging. A second radiotracer injection followed by SPECT imaging was performed 24 hours after PTCA. RESULTS: The study included 21 patients (median [interquartile range] age 70 [56-74] years, 52% male). The degree of diameter stenosis of treated vessels ranged from 60-99%, with successful PTCA performed with a mean 5-minute balloon occlusion time, resulting in ≤20% residual stenosis in all cases. The vessels undergoing PTCA were 6 in the LAD, 5 in the LCx, and 10 in the RCA. For the cohort, the size of the perfusion defect was 16 [8-30]% of the LV and the collateral perfusion at rest within the perfusion defect was 64 [58-68]% of normal perfusion within that region. Collateral perfusion was negatively correlated with perfusion defect size (R2 = 0.85, p < 0.001), but did not differ by sex (p = 0.27) or age (p = 0.58). CONCLUSIONS: This is the first study to describe the magnitude of microvascular collateral perfusion in CAD. On average, despite coronary occlusion and an absence of angiographically visible collateral vessels, collaterals provide approximately 60% of the perfusion that reaches the jeopardized myocardium during coronary occlusion. This magnitude of collateral perfusion is much higher than previously speculated. A previous study using microspheres in dogs found that collateral perfusion in the setting of an occluded vessel was 6% of normal. By comparison, the current study found ten times greater collateral perfusion in patients with CAD.